A Comment on: "State Capacity, Reciprocity, and the Social Contract" by Timothy Besley. Issue 4 (23rd July 2020) - Bowles, Samuel
Abstract : Treating civic preferences as endogenous and government policies and tax capacities as both an influence on and a consequence of their evolution is an important new strand of thinking to which Besley has contributed. I ask: Does his model provide a convincing explanation of the way that civic cultures and the expansion of the state evolved as a matter of historical fact? And I suggest a number of alternative modeling approaches that both would recognize that policy makers take account of the effects of their policy choices on preferences and, consistent with empirical observations, would support equilibria with culturally heterogeneous rather than homogeneous populations.